Chapter Le sfide globali dell'era odierna da assumere come coordinate generali - Lombardi, Mauro (Studi e saggi, 2021)
In an era characterized by uncertainty and complexity efforts must be increased to define general coordinates on which to base medium-long term strategies. To this end, it is reasonable to start with the precise identification of global challenges and then define the appropriate theoretical and operational tools to face them. Indeed this chapter deals with topics concerning the following trends: 1) smart manufacturing. 2) Constraints deriving from limited basic natural resources (water, energy, food). 3) Potentialities and risks of artificial intelligence developments. 4) Changes in the workplace as a result of the increasing use of AI. 5) Suggestions on how to rethink work through two trajectories and one operational trail.